Five-year Prevalence of Gastrointestinal Diseases and Disorders in Akure South, Nigeria: Prevalence of Gastrointestinal Diseases in Akure South (African Journal of Biomedical Research, 2021)
The burden of gastrointestinal diseases and disorders (GIDD) remains high in Nigeria and varies across regions. This study was therefore designed to examined the prevalence of gastrointestinal diseases and disorders over a period of 5-years from January 2014 to December 2018 in Akure South of Ondo state, Nigeria. Descriptive retrospective study was employed and the medical records of all patients diagnosed for GIDD in the two selected health facilities were reviewed within the study period. In total, 12,323 medical records of patients with GIDD were included in this study. The prevalence of GIDD were 44.9% in the year 2014 with the lowest prevalence of 6.7% occurring in the year 2018. Over the 5-years period, lower GIDD cases were 91% compared to upper GIDD that was 9%. Peptic ulcer had the highest prevalence (55%) of lower GIDD followed by gastroenteritis (30%). Hiatal hernia had the highest prevalence (84%) for upper GIDD followed by dyspepsia (11%) and Gastroesophageal reﬂux disease (5%). Over a 5-year period, the prevalence of gastrointestinal disease and disorders in Akure south in this study shows that lower GIDD is more prevalent in the study area with peptic ulcer as the most predominant GIDD among the study population.